Coronary CT angiography: Current status and continuing challenges - Sun, Zhonghua; Choo, G.; Ng, K. (British Institute of Radiology, 2012)
Coronary CT angiography has been increasingly used in the diagnosis of coronary artery disease owing to rapid technological developments, which are reflected in the improved spatial and temporal resolution of the images. High diagnostic accuracy has been achieved with multislice CT scanners (64 slice and higher), and in selected patients coronary CT angiography is regarded as a reliable alternative to invasive coronary angiography. With high-quality coronary CT imaging increasingly being performed, patients can benefit from an imaging modality that provides a rapid and accurate diagnosis while avoiding an invasive procedure. Despite the tremendous contributions of coronary CT angiography to cardiac imaging, study results reported in the literature should be interpreted with caution as there are some limitations existing within the study design or related to patient risk factors. In addition, some attention must be given to the potential health risks associated with the ionising radiation received during cardiac CT examinations. Radiation dose associated with coronary CT angiography has raised serious concerns in the literature, as the risk of developing malignancy is not negligible. Various dose-saving strategies have been implemented, with some of the strategies resulting in significant dose reduction. The aim of this review is to present an overview of the role of coronary CT angiography on cardiac imaging, with focus on coronary artery disease in terms of the diagnostic and prognostic value of coronary CT angiography. Various approaches for dose reduction commonly recommended in the literature are discussed. Limitations of coronary CT angiography are identified. Finally, future directions and challenges with the use of coronary CT angiography are highlighted.